Young Risk Takers: Alcohol, Illicit Drugs, and Sexual Practices among a Sample of Music Festival Attendees. (11th December 2014) - Jenkinson, Rebecca; Bowring, Anna; Dietze, Paul; Hellard, Margaret; Lim, Megan S. C.
Abstract : Background . Alcohol and other drug use and sexual risk behaviour are increasing among young Australians, with associated preventable health outcomes such as sexually transmissible infections (STIs) on the rise. Methods . A cross-sectional study of young people's health behaviours conducted at a music festival in Melbourne, Australia, in 2011. Results . 1365 young people aged 16–29 completed the survey; 62% were female with a mean age of 20 years. The majority (94%, n = 1287 ) reported drinking alcohol during the previous 12 months; among those, 32% reported "binge" drinking (6+ drinks) at least weekly. Half (52%) reported ever using illicit drugs and 25% reported past month use. One-quarter (27%) were identified as being at risk of STIs through unprotected sex with new or casual partners during the previous 12 months. Multivariable analyses found that risky sexual behaviour was associated with younger age (≤19 years), younger age of sexual debut (≤15 years), having discussed sexual health/contraception with a doctor, regular binge drinking, and recent illicit drug use. Conclusion . Substance use correlated strongly with risky sexual behaviour. Further research should explore young people's knowledge of alcohol/drug-related impairment and associated risk-taking behaviours, and campaigns should encourage appropriate STI testing among music festival attendees.